Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1103/physrevd.97.054006
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative quark, gluon, and meson correlators of unquenched QCD

Abstract: We present nonperturbative first-principle results for quark, gluon, and meson 1PI correlation functions of two-flavor Landau-gauge QCD in the vacuum. These correlation functions carry the full information about the theory. They are obtained by solving their functional renormalization group equations in a systematic vertex expansion, aiming at apparent convergence. This work represents a crucial prerequisite for quantitative first-principle studies of the QCD phase diagram and the hadron spectrum within this f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
394
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 206 publications
(436 citation statements)
references
References 105 publications
29
394
0
Order By: Relevance
“…Thus, the dominance of the scalar-pseudoscalar coupling indicating chiral symmetry breaking is solely generated by quark-gluon dynamics. This is in line with earlier RG flow studies of QCD in the vacuum limit [19,20] and it has indeed been observed that this dominance entails the formation of a corresponding chiral condensate [20,21] governing the low-energy dynamics.…”
Section: A Symmetry Breaking Patternssupporting
confidence: 91%
“…Thus, the dominance of the scalar-pseudoscalar coupling indicating chiral symmetry breaking is solely generated by quark-gluon dynamics. This is in line with earlier RG flow studies of QCD in the vacuum limit [19,20] and it has indeed been observed that this dominance entails the formation of a corresponding chiral condensate [20,21] governing the low-energy dynamics.…”
Section: A Symmetry Breaking Patternssupporting
confidence: 91%
“…Note also that Yang-Mills theory exhibits an infrared mass gap with the scale Λ QCD due to its confining dynamics. In covariant gauges, as used in the present work, this mass gap results in a mass gap in the gluon propagator, for a treatment within the current functional renormalization group (FRG) approach, see [109,110] and references therein. This dynamical gaping may be simulated here by simply identifying the infrared cutoff scale with Λ QCD .…”
Section: B Asymptotic Freedom In Yang-mills With Gravitymentioning
confidence: 99%
“…Second, being exact equations, they can only be solved once approximations are made because they form an infinitely large system of equations. In the vacuum, several studies indicate that the system has favorable convergence properties [25,[45][46][47][48][49]. However, in the medium the corresponding level of truncation is not reached yet, and once it is, it is not guaranteed that the convergence properties remain the same.…”
Section: Introductionmentioning
confidence: 99%